2022
DOI: 10.3390/s22239136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Accuracy Improvement of UWB-TDoA-Based Indoor Positioning System

Abstract: Positioning systems are used in a wide range of applications which require determining the position of an object in space, such as locating and tracking assets, people and goods; assisting navigation systems; and mapping. Indoor Positioning Systems (IPSs) are used where satellite and other outdoor positioning technologies lack precision or fail. Ultra-WideBand (UWB) technology is especially suitable for an IPS, as it operates under high data transfer rates over short distances and at low power densities, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In the second trial, the distance error measurement was 0.97 m for the y coordinate and 0.51 m for the x coordinate. Several factors could have contributed to the distance error observed in the second trial, including the orientation of the anchor's antennas, as suggested by Grasso et al [22]. Their study found that positioning accuracy could be improved by directing the anchor's antennas toward the center of the area being covered, resulting in distance errors of 5 cm for dynamic measurements and 15 cm for static measurements.…”
Section: Static Positioning Experimentsmentioning
confidence: 81%
“…In the second trial, the distance error measurement was 0.97 m for the y coordinate and 0.51 m for the x coordinate. Several factors could have contributed to the distance error observed in the second trial, including the orientation of the anchor's antennas, as suggested by Grasso et al [22]. Their study found that positioning accuracy could be improved by directing the anchor's antennas toward the center of the area being covered, resulting in distance errors of 5 cm for dynamic measurements and 15 cm for static measurements.…”
Section: Static Positioning Experimentsmentioning
confidence: 81%
“…In this way, three or more localization base stations are required to determine the location of the target to be measured [16]. ,1 i d represents the difference in distance from the target M to the primary base station, and each of the secondary base stations is defined as follows (2):…”
Section: Srd Model Based On Tdoa Algorithmmentioning
confidence: 99%
“…Indoor Positioning Systems (IPSs) are crucial in diverse fields, from emergency services to industrial automation [1]. The most used satellite technologies, like the Global Navigation Satellite System (GNSS) [2], are ineffective indoors due to signal attenuation caused by building materials and environmental factors [3]. Ultra-wideband (UWB) technology has been increasingly recognized as an efficacious strategy for IPSs due to its high accuracy, low transmission cost, and robustness to environmental perturbations [4].…”
Section: Introductionmentioning
confidence: 99%